The Influence of Online Games on Junior High School Students in North Sumatera Province - Gilang Surya Amanda; Ade Risma; Muhayni Amalia; Muhammad Fathlinnas Siregar; Annisa Arrumaisyah Daulay (Edumaspul: Jurnal Pendidikan, 2022)
This study discusses the effect of online games on junior high school students in Tanjung Morawa sub-district, Deli Serdang district. The influence of online games can cause physical, mental and mental damage to junior high school students in general. In addition, changes in the behavior of students who are addicted to online games are not felt, but can be felt by people in the environment, especially parents. Children's social personality can be felt by people in the environment, especially parents. This study used qualitative research, the object of research was students aged 14-16 years in junior high school in Bandar Labuhan Village, Tanjung Morawa District, Deli Serdang Regency. This data is interviewed and the reality at school. The analysis includes research results and conclusions. This research proves that online game addiction can affect the personality of junior high school students, namely aggressive traits and attitudes, competition between friends, disputes/quarrels between friends, cooperative attitude, egotistical, he will focus on the game and not think about the environment around him.